Effectiveness of coffee husk ash and coconut fiber in improving peat properties - Siti Azela, Mazlan; Dayang Zulaika, Abang Hasbollah; Mariatul Kiftiah, Ahmad Legiman; Aizat, Mohd Taib @ Taib; Aniza, Ibrahim; Ahmad Bukhari, Ramli; Siti Norafida, Jusoh; Norinah, Abdul Rahman; Mohd Firdaus, Md Dan; Azhani, Zukri (Elsevier Ltd, 2023)
Peat is a well-known problematic soil associated with poor engineering properties because its engineering with low shear strength, highly compressible, high moisture content. The characteristics make it unsuitable for construction in its natural stage. Thus, this study determines the soil properties of untreated peat soil and assesses the changes in strength of the treated peat soil using the admixture of Coffee Husk Ash (CHA) and Coconut Fibre (CF). The percentage of CF used is 0.50%, 0.75% and 1.0% meanwhile the percentage of CHA used was 5%, 6%, and 7% by the weight of the soil sample. The peat soil for this study were retrieved from Mardi Pontian in Johor. Soil properties such as moisture content, bulk density, and the Atterberg limit have been tested. The result of the Standard Proctor test in this study determined the Optimum Moisture Content and Maximum Dry Density of soil samples. The strength of these samples has been determined by using the Unconfined Compressive Strength (UCS). The physical properties for untreated peat soil with the moisture content of 250%, organic content about 77%, the specific gravity was in the range of 1.48–1.8. The Atterberg limit for liquid limit is 230. The compaction test results has shown decrement in maximum dry density (MDD) but an increase in strength with the addition of CHA and CF in peat soil. According to the findings, 0.5% of Coconut Fiber improves the engineering properties of peat soil (CF).